Unprocessed wheat γ‐gliadin reduces gluten accumulation associated with the endoplasmic reticulum stress and elevated cell death. Issue 1 (22nd July 2022) - Chen, Qian; Yang, Changfeng; Zhang, Zhaoheng; Wang, Zihao; Chen, Yongming; Rossi, Vincenzo; Chen, Wei; Xin, Mingming; Su, Zhenqi; Du, Jinkun; Guo, Weilong; Hu, Zhaorong; et al.
Summary: Along with increasing demands for high yield, elite processing quality and improved nutrient value in wheat, concerns have emerged around the effects of gluten in wheat‐based foods on human health. However, knowledge of the mechanisms regulating gluten accumulation remains largely unexplored. Here we report the identification and characterization of a wheat low gluten protein 1 ( lgp1 ) mutant that shows extremely low levels of gliadins and glutenins. The lgp1 mutation in a single γ‐gliadin gene causes defective signal peptide cleavage, resulting in the accumulation of an excessive amount of unprocessed γ‐gliadin and a reduced level of gluten, which alters the endoplasmic reticulum (ER) structure, forms the autophagosome‐like structures, leads to the delivery of seed storage proteins to the extracellular space and causes a reduction in starch biosynthesis. Physiologically, these effects trigger ER stress and cell death. This study unravels a unique mechanism that unprocessed γ‐gliadin reduces gluten accumulation associated with ER stress and elevated cell death in wheat. Moreover, the reduced gluten level in the lgp1 mutant makes it a good candidate for specific diets for patients with diabetes or kidney diease.